1987
DOI: 10.1620/tjem.151.275
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between gastric emptying time and the response of pancreatic polypeptide to test meals in peptic ulcer diseases.

Abstract: Hospital of Japanese National Railways, Sendai 980 KOIZUMI, F., KAWAMURA, T., ISHIMORI, A., EBINA, II. and SATOH, M. Correlation between Gastric Emptying Time and the Response of Pancreatic Polypeptide to Test Meals in Peptic Ulcer Diseases. Tohoku J. exp. Med., 1987, 151(3), 275-281 In the present study, pancreatic polypeptide (PP) levels both in basal state and after stimulation by meal were determined in 21 controls, 28 patients with gastric ulcer and 21 patients with duodenal ulcer and their correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…1, the plasma acetami nophen concentration in a control study was increased time dependently and peaked at 45 min (6.9 ± 1.2,ug/ml) after the acetami nophen administration. Our results were con sistent with those reported by Koizumi et al who measured gastric emptying in dogs by the acetaminophen method (14). This means that the food containing acetaminophen was grad ually emptied from the stomach, and acetami nophen was absorbed in the small intestine.…”
Section: Gastric Emptying In the Dogsupporting
confidence: 91%
“…1, the plasma acetami nophen concentration in a control study was increased time dependently and peaked at 45 min (6.9 ± 1.2,ug/ml) after the acetami nophen administration. Our results were con sistent with those reported by Koizumi et al who measured gastric emptying in dogs by the acetaminophen method (14). This means that the food containing acetaminophen was grad ually emptied from the stomach, and acetami nophen was absorbed in the small intestine.…”
Section: Gastric Emptying In the Dogsupporting
confidence: 91%
“…In the present study, however, diabetic hyperglycemia was not correlated with delayed gastric emptying. Furthermore, it was reported that gastric emptying in STZ-induced diabetic gastroparetic dogs did not improve with control of blood glucose by insulin [25].…”
Section: Discussionmentioning
confidence: 99%